Juridical Review of Money Laundering with Terrorism - Adhalia Septia Saputri (International Journal of Social Service and Research, 2023)
Money laundering and terrorism are often related to each other because money from crime can be used to finance terrorist activities and money laundering can be used to disguise the origin of the money. In order to overcome these two crimes, cooperation between law enforcement agencies and good international coordination is needed. In Indonesia, money laundering is regulated in Law Number 8 of 2010, while terrorism is regulated in Law Number 15 of 2003. Some of the legal issues that are still current in the effort to combat money laundering and terrorism include the implementation of the Financial Transaction Reporting System, the designation of terrorist crime organizations, the exchange of information between law enforcement agencies, the protection of informants and witnesses, and the implementation of new laws on money laundering. International cooperation is essential in efforts to overcome this problem. Strong cooperation is expected to cut off the flow of terrorism funds and reduce the risk of criminal acts entering the financial system and help combat terrorism cases that can harm national security.